Hubungan Pengetahuan dan Sikap dengan Perilaku Merokok Penghuni Asrama Mahasiswa Islam Sunan Gunung Jati Jakarta Timur - Sahruni Sahruni; Elwindra Elwindra (Jurnal Persada Husada Indonesia, 2016)
Smoking behavior seen from different angles is very harmful, both for the individual and others in the vicinity. At the time of smoking person smokes more than 4000 harmful chemicals. The dangerous substances are nicotine, tar, carbon monoxide (CO), and other toxic chemicals. Diseases that can be caused by smoking is not just a minor ailments such as cough and shortness of breath, but also death. The research aimed to determine the relationship of knowledge, attitude and behavior of the occupants smoke Islam Student Dormitory Sunan Gunung Jati, East Jakarta. This research is analytic survey using cross sectional design with a sample of 81 people. The results using the chi square test found no significant relationship between independent variables and the dependent variable, so that no significant relationship between the characteristics of respondents (age, national origin, universities, faculty / study program, the length of stay at the hostel) as well as knowledge and attitudes against smoking behavior. Suggested for further research to be carried out interviews with respondents covered at the time of the study, so the bias is known more uncertain variables that influence smoking behavior of respondents.